Pengembangan Pemikiran Pendidikan Islam Pada Periode Sebelum Indonesia Merdeka (1900-1945) - Rahmawati Rahma; Royhain Iqbal; Mohammad Hasan (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
The process of the arrival of Islam in Indonesia can be understood from various opinions that can historically be explained in several theories below: Indian theory, Persian theory, theory, China, and Arab theory. The idea of education in Islam during the Dutch colonial period in Indonesia was that the Dutch colonial government severely restricted the activities of madrassas and teachers who taught in madrassas. They do so because of the growing fear of Muslims. The idea of education in Islam during the Japanese colonial period in Indonesia Islamic education is slightly freer than during the Dutch colonial rule. However, Japan with its mission, requires teachers to learn Japanese in giving lessons and changing Dutch to Indonesian, including requiring respect to Tenno (Emperor) and will be arrested if they do not follow the rules of the Japanese colonial side.